Restoration management of cattle resting place in mountain grassland - Kassahun, Teowdroes; Pavlů, Klára; Pavlů, Vilem; Pavlů, Lenka; Novak, Jan; Blažek, Petr (PloS one, 2021)
This study investigated the effect of restoration management of a weed-infested area, previously used as cattle resting place, on herbage production and nutrient concentrations in the soil and herbage. The experiment was undertaken from 2004 to 2011 at the National Park of Nízké Tatry, Slovakia. Three treatments were applied: (i) cutting twice per year, (ii) herbicide application, followed after three weeks by reseeding with a mixture of vascular plant species and then cut twice per year, and (iii) unmanaged. Treatments had significant effect on biomass production and concentration of nutrients in the soil and in herbage. Nutrient concentrations in herbage and in soil declined progressively under the cutting treatments and reached optimum ranges for dairy cattle at the end of the experiment when herbage N was less than 15 g kg-1 and herbage P was 3.4 g kg-1. There was also a strong positive relationship under the cutting treatments between soil nutrient concentrations and herbage nutrient concentrations for N, P, K, Mg and Ca. Although the cutting management as well as the combination of herbicide application with cutting management reduced nutrient concentrations in the soil and in herbage, the nutrient concentrations remained relatively high. We can conclude that restoration of grassland covered with weedy species like Urtica dioica and Rumex obtusifolius, with excessive levels of soil nutrients, cannot be achieved just by cutting and herbicide application.
Keywords: Cattle; Animals; skot; draslík; Grassland; Nitrogen; Potassium; Biomass; Slovakia; pastviny; Poaceae; lipnicovité; regenerace a remediace životního prostředí; Slovenská republika; zvířata; Environmental Restoration and Remediation; půda; Soil; biomasa; dusík